Pengaruh Model Pembelajaran Scramble Bermuatan Literasi Sains terhadap Kompetensi Belajar Peserta Didik pada Materi Sistem Pernapasan Manusia di SMPN 13 Padang - Kresy Monery Sitompul; Siska Alicia Farma; Syamsurizal (Pedagogi Hayati, 2019)
This research is based on the problems that exist in SMPN 13 Padang, namely the learning model that is less varied, students learning abilities are still low, teacher-centered learning. The effort that can be done to apply the scramble learning model with science literacy in the human respiratory system at SMPN 13. The purpose of this research was to determine the effect of applying the scramble learning model with scientific literacy on the learning competencies of grade VIII students of SMP 13 Padang. This research was an experimental research with a randomized control group posttest only design. The study population was grade VIII students of SMP 13 Padang in the 2018/2019 academic year which spread to eight classes. The research sample was taken using purposive sampling. The results were selected class VIII.3 as the experimental class and class VIII.2 as the control class. The hypothesis in this study was tested using the t-test. The results of the study using the t-test can be concluded that the competency of students knowledge about the value of tcount 2.83> ttable 1.67, the competency attitudes of tcount 5.77> ttable 1.67, and competency skills of tcount 1.91> ttable 1.67. This point that the hypothesis is accepted. So, it can be concluded that the application of the scramble learning model with scientific literacy can improve the competency of knowledge, attitudes, and skills of grade VIII students of SMP 13 Padang. ABSTRAK: Penelitian ini didasarkan pada permasalahan yang ada di SMPN 13 Padang, yaitu model pembelajaran yang kurang beragam, kemampuan belajar siswa masih rendah, pembelajaran yang berpusat pada guru. Perlu upaya untuk menerapkan model pembelajaran dengan orientasi literasi sains dalam sistem pernapasan manusia di SMPN 13. Tujuan penelitian ini adalah untuk menguji dampak penerapan model pembelajaran dengan literasi sains terhadap kompetensi belajar siswa kelas VIII SMP 13 Padang. Penelitian ini adalah penelitian eksperimental dengan randomized control group posttest only design. Populasi dalam studi ini adalah siswa kelas VIII SMP 13 Padang pada tahun akademik 2018/2019 yang menyebar ke delapan kelas. Sampel penelitian diambil dengan menggunakan purposive sampling. Hasil yang dipilih adalah kelas VIII. 3 sebagai kelas eksperimental dan kelas VIII. 2 sebagai kelas kontrol. Hipotesis dalam studi ini diuji menggunakan t-Test. Hasil penelitian menggunakan t-Test dapat disimpulkan bahwa kompetensi siswa dengan nilai t-hitung 2,83 > t-tabel 1,67, kompetensi sikap dengan t-hitung5,77 > t-table 1,67, dan keterampilan dengan t-hitung 1,91 > t-tabel 1,67. Dengan demikian hipotesis alternative diterima. Sehingga dapat disimpulkan bahwa penerapan model pembelajaran dengan literasi sains dapat meningkatkan kompetensi pengetahuan, sikap, dan keterampilan siswa kelas VIII SMP 13 Padang.